CONSTRUCTING A MATHEMATICAL MODEL FOR ONE-DIMENSIONAL DIFFERENTIAL CORRELATOR - Vladimir P. Gerasimov; Alexander Yu. Darzhanya; Vladimir D. Kovalev (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with mathematical modeling of the algorithm for calculating the error between the current and desired position of the vision line along one of the axes of the on-board controller in the videovisira of unmanned aerial vehicle (UAV), which allows an automatic increase in the reliability and accuracy of fire detecting and tracking in emergencies.